Dual versus Administrative Federalism: Origins and Evolution of Two Models. Issue 4 (10th March 2022) - Mueller, Sean; Fenna, Alan
Abstract: Federations have traditionally divided powers either along policy lines, in which case a dual system results, or along functional lines with the central government legislating and the constituent units implementing, in which case a system of administrative federalism results. Although this distinction is widely used, we know little of its specific origins, the degree to which it accurately portrays federal practice today, or even its implications. This article examines the origins and traces the evolution of these two models in six federations since their formation: the United States, Switzerland, Canada, Australia, Germany, and India. Two questions are addressed. First, what explains the choice for either the one or the other type, and is administrative federalism really sui generis to Germany, as often argued in the literature? And second, how have they evolved over time and has there been a convergence?